The Ontogenetic Development Of Study Activity: A Literature Review - Joaquim Mendonca, Ana Barbara; Leonardo, Nilza Tessaro; Ferreira Asbahr, Flavia da Silva (Cdid-centro Documentacion, Investigacion & Difusion, 2021)
The present article, based on Historical-Cultural Psychology, aims to clarify the ontogenetic development of the study activity, the guiding activity of the school age, covering its transition period, content, structure and neoformations. For this, a bibliographic review was made that included studies by the following Soviet psychologists: Bozhovich, Davidov, Elkonin, Galperin, Leontiev, Markova, Vigotski and Zaporozhets. From this study it was possible to notice the close relationship between education and psychic development. Thereby, it is expected that this text will contribute to the understanding of the subject of learning, since the clarity about the child's guiding activity brings with it new perspectives to the pedagogical practice.
Keywords: Study activity; School age; Historical-Cultural Psychology; Human Development